Teacher profile from the emerging dimensions in distance education, UNED of Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2024)
The study consolidates the development of a profile of university teaching staff, considering the emerging dimensions of distance education models, stemming from significant changes brought about by the pandemic.The research methodology is systemic, employing a mixed descriptive approach with both quantitative and qualitative characteristics. The fieldwork identifies a population comprising chair coordinators, to gather quantitative information using survey techniques. Following data collection, categories are identified that will inform the design of qualitative data collection, employing directed interview techniques with four chair coordinators selected based on specific criteria.The study considers research lines related to teaching profiles that align with educational scenarios, which have currently evolved in parallel with technological changes.
Keywords: distance education; teaching profile; digital competencias; pedagogical model